PTU-278 Transanal endoscopic microsurgey: the impact of colorectal cancer screening on patient demographics and pathological characteristics in a single cent\\re. (22nd June 2015) - Proctor, M; Ekatah, GE; Stewart, A; Reddy, CT; Anderson, DN; Speake, D
Abstract : Introduction: The Bowel Screening Programme aims to detect polyps and cancers at an earlier stage, many of these lesions are early rectal cancers or polyps not amenable to endoscopic therapy. Surgical Resection carries significant morbidity; consequently Transanal Endoscopic MicroSurgery (TEMS) has gained popularity. We investigate the impact of screening on TEMS activity in a single centre. Method: Data on all patients undergoing TEMS for rectal lesions between 2010 and 2014 was prospectively collected. Patient characteristics and TEMS pathological data were investigated. Statistical analysis was carried out using independent T-test and Chi Square analysis. Results: It total, 97 patients underwent TEMS resection for rectal lesions, 18 of which had evidence of cancer. There was no difference in the proportions of malignancies in those identified through screening (n = 5 (17%); pT1 (n = 2), pT2 (n = 2), pT3 (n = 1)) when compared to the non-screening cohort (n = 13 (19%); pT1 (n = 7), pT2 (n = 4), pT3 (n = 2)). Patients identified through the screening process (n = 29, 30%) were younger (mean 66–71, p = 0.04), had smaller benign lesions (maximal diameter mean 34 mm to 48 mm, p = 0.012) and smaller cancers (maximal diameter mean 22 mm to 41 mm, p = 0.04). Conclusion: Screen detected rectal lesions account for approximately a third of all those TEMS procedure performed in a single unit. Patients detected through screening were younger with smaller lesions. The advent of screening has increased work load for TEMS and this demand on the service is likely to increase in the future. Disclosure of interest: None Declared.